Development Communication in Post-Conflict Societies: Building Trust and Social Cohesion - Syarifuddin, Syarifuddin; Sulistiani, Indah; Fuaddin, Muhammad; Irawati, Irawati (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2026)
Post-conflict community development demands communication strategies capable of bridging social divisions, restoring trust, and strengthening social cohesion in vulnerable environments. This study aims to analyze the role of development communication in facilitating inclusive dialogue, disseminating accurate information, and fostering community participation in the reconciliation process. Using a qualitative approach through document analysis, in-depth interviews, and case studies in several post-conflict areas, this study identifies the most effective communication mechanisms for rebuilding damaged social relations. The results indicate that development communication serves as a crucial medium for building a shared narrative, reducing intergroup tensions, and fostering mutual trust through transparency and public participation. Strategies that integrate local media, facilitate intergroup dialogue, and strengthen the capacity of community actors have been shown to increase community involvement in the recovery process. Furthermore, the use of modern communication technology accelerates information distribution and expands safe spaces for interaction for previously marginalized groups.